Foundations of Industrial Development: Gender Dimensions in Markets and Industries in Purwokerto - Suci Hanani; Fani Annisa Putri; Faizza Dini Sahila; Naerul Edwin Kiky Aprianto (PT. Gyandharma Global Media, 2025)
Industrial development is not only oriented toward economic growth but also toward social justice through gender equality. This study aims to analyze women’s contributions to industrial development in Purwokerto, identify opportunities and challenges they face, and formulate gender-responsive industrial development strategies. The research employs a descriptive qualitative method based on secondary data analysis, with sources from the Central Bureau of Statistics (BPS), the Ministry of Women’s Empowerment and Child Protection (KPPPA), the Banyumas Office of Cooperatives and SMEs, as well as scholarly literature and reliable media. The analysis applies a gender dimension framework covering access, participation, and control. The results show that women’s participation in Central Java has increased, reflected in the rising Female Labor Force Participation Rate (FLFPR) and improvements in the Gender Development Index (GDI). In Purwokerto, over 60% of SMEs are managed by women, particularly in culinary, trade, handicrafts, and traditional markets, positioning them as key drivers of the local economy. Opportunities to strengthen women’s roles are evident through business digitalization and the growth of the halal industry, supported by local government programs. However, major challenges remain, including limited access to finance, low digital literacy, double domestic burdens, and underrepresentation in large-scale industries. Therefore, gender-responsive industrial strategies are needed by expanding financial access, enhancing digital and managerial capacities, and promoting affirmative policies to increase women’s representation in strategic positions. Thus, Purwokerto has the potential to become a model of inclusive and sustainable industrial development.